Makna Perayaan Ekaristi Terhadap Pemulihan Korban Adiksi Narkoba di Rehabilitasi ‘Rumah Kita’ - Liana Sianturi (Fakultas Teologi, Universitas Sanata Dharma, 2025)
Drug addicts are typically considered as morally, spiritually, and physically shattered individuals. Pastoral care is provided through the existence of the KSSY-managed drug recovery clinic